“For Them, Not Us”: How Ableist Interpretations of the International Symbol of Access Make Disability - Jones, Chelsea (Critical Disability Discourses, 2013)
This paper uses a cultural studies lens to suggest that the ISA confers a semiotic imposition of “otherness” upon people with disabilities by signaling dominant, ableist cultural ideologies. Considering disability as representative of the culture in which it appears, the ISA’s sometimes troubling manifestations emerge at certain intersections of our cultural landscapes where us and them meet and separate. This paper focuses on the disabled and non-disabled experiences through the author’s self-reflexivity, and through the work of Liat Ben-Moshe and Justin Powell, as it queries the social spaces which inhabit and exclude the ISA as a cultural object tied to disability-related mythologies. The manifestations of this symbol in the author’s cultural landscape hold political and social meanings that lead her to think about disability as a way of being in relation to others. The ISA can be read by spectators as sponsoring a highly problematic message about embodiment, binaries, and boundaries stemming from interpretations of the body in an ableist, Western culture.Keywords: International Symbol of Access (ISA), accessibility, disability semiotics, disability mythologies